„Virtuální etnografická procházka“ jako příklad vedení etnografického výzkumu v době internetu - Marie Dlouhá (AntropoWebzin)
Ethnography is usually defined as a method (or set of methods), or as a research paradigm. The existence of multiple definitions is partly the result of ethnography being used by researchers from different fields of study; sociologists and anthropologists, for example. The purpose of this article is to try and determine whether a “new ethnography” really exists. While ethnography originally involved face-to-face contact, technological developments (especially the invention of the internet) have made interacting in virtual spaces possible. The author presents a specific application of ethnographic methods in the age of internet communication which she dubs “a virtual ethnographic tour”. She demonstrates that the main characteristic that ethnography retains from its classical form is the close link between theory and methodology. In contrast, a specific application is always new because social reality is constantly changing.